Artificial Intelligence: Optimizing The Recruitment Process - Abdurrahim, Abdurrahim (Cebong Journal, 2024)
This study aims to explore the role and potential of artificial intelligence (AI) in the recruitment process in an increasingly complex digital era. Using the Narrative Literature Review method, this research summarizes and analyzes various relevant literature sources related to the use of AI in recruitment. The findings indicate that AI enhances efficiency and effectiveness in candidate search and selection, with the ability to analyze data quickly and accurately. Additionally, AI contributes to reducing bias in decision-making, creating a more objective and transparent process. However, challenges such as potential algorithmic bias and privacy issues still need to be addressed. With proper implementation, AI not only helps organizations find suitable candidates but also promotes a fairer and more inclusive recruitment process. This study provides valuable insights for HR practitioners and stakeholders in adopting AI technology in recruitment.